Search for empathy: poverty porn popular culture in Indian television - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2023)
The bipolar political conditioning in the Cold War era was perfect for media discourses to find propagandist methods to frame stories in ways that help set special agendas. The coloniser's curiosity for the indigenous and ritualistic cultural forms of these lands was a sign of exploitation rather than inclusion; the looting and importing of natural resources and artistic assets from colonised regions attest to the desire for things that had pure materialistic value. The revulsion associated with the visual perception of these "outside spaces" is fundamental to the construction of power dominance as it signifies notions of social acceptance and rejection. [...]the notion of "disgust" gets associated with the body of the colonised Other, and the representations of the "disgusted other" essentialises cultural identities.
Keywords: visual perception; popular culture; empathy; cultural identity